2019
DOI: 10.1038/s41598-019-41287-x
|View full text |Cite
|
Sign up to set email alerts
|

Dry season habitat use of fishes in an Australian tropical river

Abstract: The modification of river flow regimes poses a significant threat to the world’s freshwater ecosystems. Northern Australia’s freshwater resources, particularly dry season river flows, are being increasingly modified to support human development, potentially threatening aquatic ecosystems and biodiversity, including fish. More information is urgently needed on the ecology of fishes in this region, including their habitat requirements, to support water policy and management to ensure future sustainable developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 69 publications
1
18
3
Order By: Relevance
“…The results of the current study demonstrate that juvenile Sooty grunter exhibit a strong preference for shallow, fast flowing hydraulic habitat during the dry season. These findings are broadly compatible with those of previous studies by Chan et al (2012) and Keller et al (2019), who both concluded that they prefer shallow, fast flowing riffle areas and that preservation of riffles during the dry season is critical to the viability of Sooty grunter populations. However, while Chan et al (2012) emphasised the importance of riffle habitat for juvenile Sooty grunter, their analyses suggested optimal velocities of 0–0.6 m s −1 and depths of 0.3–0.6 m (Table 4).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of the current study demonstrate that juvenile Sooty grunter exhibit a strong preference for shallow, fast flowing hydraulic habitat during the dry season. These findings are broadly compatible with those of previous studies by Chan et al (2012) and Keller et al (2019), who both concluded that they prefer shallow, fast flowing riffle areas and that preservation of riffles during the dry season is critical to the viability of Sooty grunter populations. However, while Chan et al (2012) emphasised the importance of riffle habitat for juvenile Sooty grunter, their analyses suggested optimal velocities of 0–0.6 m s −1 and depths of 0.3–0.6 m (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…A particular concern for water management is that the availability of shallow, fast flowing habitat may be reduced due to increased groundwater abstraction in the dry season, a period when river flows are at their lowest and water abstraction is likely to have its greatest effects (King et al, 2015). Although previous research suggests that juvenile Sooty grunter exhibit a strong preference for shallow, fast flowing habitat during dry season, low‐flow periods (Chan et al, 2012; Keller et al, 2019), these studies have several potential limitations, in that they (1) did not consider diel variation in habitat use (see Davey et al, 2011), (2) developed habitat suitability curves using data from different electrofishing methods (backpack in riffles, boat‐mounted in other habitats) and (3) estimated habitat preference using fish abundance and habitat data that were not spatially matched. The fish abundance data were catch‐per‐unit effort (CPUE) calculated over 5‐min electrofishing ‘shots’ covering an average river length of 77 m (range: 5–263 m), with five replicate measures of depth and velocity taken within each sampled reach (Chan et al, 2012; Keller et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations